Applying BIM and pedestrian simulation for architectural flow line optimization in subway stations: an empirical analysis at Chongqing Ranjiaba Station - Xian Li; Ziyi Zhao; Xudong Zeng (Journal of Asian Architecture and Building Engineering)
In China’s new urbanization, urban rail transit has developed rapidly. Multiline subway stations in Chongqing face issues such as high passenger flow and intersecting pedestrian flows, leading to congestion, which affects station safety and service quality. This study aims to optimize subway station architectural flow lines, defined as pathways facilitating pedestrian movement within stations, to meet passenger demands, improve service quality, and contribute to smart city development. Combining BIM technology with pedestrian simulation, this research uses quantitative data analysis to optimize subway station flow lines under non-emergency conditions, a scenario rarely addressed in existing studies that focus on emergency evacuations, and proposes optimization strategies. We constructed an optimization framework based on BIM and pedestrian simulation and conducted an empirical study at Chongqing Ranjiaba Station to verify its feasibility. This research systematically examines subway station entry, exit, and transfer systems through literature reviews, surveys, simulations, and case studies. The analysis, within the context of smart city development and transit-oriented design, identifies issues in station layout and pedestrian flow, proposing and validating optimized design schemes. The study introduces a BIM-based framework for optimizing subway station flow lines, demonstrating improvements in pedestrian safety, operational efficiency, and user experience, offering practical solutions.